Intermittent Suprasternal Neck Mass Caused by Herniation of Ectopic Thymus: Report of Two Cases - Tey, Kai-Jun (Iran J Otorhinolaryngol, 2020)
INTRODUCTION: Ectopic thymus is an uncommon cause of neck masses in children that frequently present as lateral cervical swelling especially on the right side. CASE REPORT: We report two cases with atypical clinical presentation of ectopic thymus and superior herniation of normal thymus. Both of the patients manifested as intermittent midline mass at the suprasternal region during Valsalva manuevre. Unique ultrasound features with the location along the thymic descent together with dynamic assessment of the organ movement were essential to reach the correct diagnosis. Conservative approach was considered in these patients considering the necessity of thymus in the process of puberty. CONCLUSION: High index of suspicion is of utmost importance when encounter patient with similar clinical manifestation to avoid unnecessary diagnostic modalities and surgeries. Accurate diagnosis will also alleviate parents’ anxiety.